PELAKSANAAN METODE RESITASI DALAM MENINGKATKAN KEAKTIFAN PEMBELAJARAN - Sutama, Ari Sulistya; Ninghardjanti, Patni; Widodo, Jumiyanto (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
This qualitative study aimed to find out: How implementation recitation method used to improve the activity learning; obstacles encountered in implementing the method of recitation; Efforts are made in order to increase the learning activity. sources of data from informants, events and documents. Sampling techniques purposive sampling and snow ball sampling. Data collection interview, observation and documentation. The validity of the data with techniques Data triangulation and triangulation methods. Analysis of the data analysis techniques interactive. The results showed that: Implementation methods Recitation includes: Provision of duty and their teachers assign tasks instructions after explaining the material. Execution of tasks that teachers provides the opportunity for students to try to do the task according to their ability. Accountability of duty for teachers corrected simultaneously assess the results of student work. barriers to implementation recitation method: Students are bored. Students lazy to do task. The teacher gives the task a difficult language to understand. Facilities owned less supportive of learning in teaching. Effort performed: The teacher gives the task with varying types of tasks. Teachers apply the principle of reward and punishment. Teacher explains one a matter of simple language. The school replace computers which is not feasible. Keywords: Method of Recitation, Activeness of Learning